South Asia, vision & perspective : South Asian regional dialogue. - Independent Planning Commission of Pakistan (Lahore, Pakistan: Independent Planning Commission of Pakistan, 1994)
Papers presented at South Asian Regional Dialogues, during 1991-1993.
Keywords: South Asian cooperation -- Congresses; South Asia -- Politics and government -- Congresses